P085 CLINICAL AND LONGITUDINAL PATIENT REPORTED OUTCOMES AFTER TRANSVERSUS ABDOMINIS RELEASE: A SINGLE SURGEON EXPERIENCE. (25th November 2021) - Christopher, Adrienne; Morris, Martin; Barrette, Louis-Xavier; Broach, Robyn; Fischer, John
Abstract: Aim: Posterior component separation with transversus abdominis release (TAR) is a novel complex abdominal wall repair technique that maximizes medial myofascial flap advancement in a vascularized, pre-peritoneal plane. Here, we add to a growing body of literature on this technique by assessing longitudinal clinical and patient reported outcomes (PROs) after ventral hernia repair (VHR) with TAR. Material and Methods: Adult patients undergoing VHR with TAR between 10/1/2015 and 01/15/2020 by a single surgeon were retrospectively identified. Patients with parastomal hernias and <12 months of follow-up were excluded. Clinical outcomes and PROs using the Abdominal Hernia Questionnaire (AQH) and Hernia Related Quality of Life Survey (HerQLes) were assessed. Results: 57 patients were included with a median age and body mass index of 60 and 30.6 kg/m 2, respectively. The average hernia defect was 384 cm 2 [IQR 205-471], and all patients had retro-muscular mesh placed. The most common complications were delayed healing (19.3%) and seroma (14.0%). One patient required return to the OR for management of a complication and there were no cases of mesh infection or explantation. Previous hernia repair and concurrent panniculectomy were risk factors for developing any complication (p < 0.05). One patient (1.8%) recurred at a median follow-up of 25.7 months [IQR 18.2-42.1]. Significant improvement in disease-specific PROs was observed and maintained throughout the follow-up period (pre to post p < 0.05). Conclusions: Longitudinal clinical and patient-reported outcomes after VHR with TAR are limited. We conclude that TAR is a safe and efficacious adjunct in the repair of complex hernia defects.